Perspectivas teóricas y metodológicas sobre creatividad en Educación STEAM: una revisión sistemática - Pabón-Rúa, Jhon-Daniel; López-Ríos, Sonia-Yaneth; Cardona-Zapata, M´´onica-Eliana (Revista Científica, 2024)
STEAM (science, technology, engineering, arts, and mathematics) education strives towards the comprehensive training of creative and innovative individuals, but few studies address this issue. This paper presents a systematic review of the literature from databases such as Scopus, Web of Science, Science Direct, and ERIC, which found 45 units of analysis between 2010 and 2024 (August) that evaluate the creativity of students within the framework of STEAM proposals. These units of analysis allow identifying that 1), starting in 2015, there is an increase in the number of studies that evaluate creativity in the context of STEAM education, mainly in Asia and America; 2) most of the research (53.3%) conceives STEAM education as an interdisciplinary educational approach that, with the incorporation of art, favors the development of creativity, which is understood as an activity involving the production of something novel and original (46.6%) and as an unprecedented and effective way to solve problems (37.7%); 3) 55.5% of the research evaluates creativity from a psychological perspective, wherein quantitative studies prevail (55.5%) over qualitative ones (22.2%); and 4) the most used didactic strategies are project-based learning and inquirybased learning. The results suggest that STEAM is conceived as an interdisciplinary educational approach with great potential for developing creativity, which was assessed based on predominantly quantitative and individualized instruments. It is necessary to explore qualitative methodologies and sociocultural and systemic approaches in STEAM education that allow analyzing creative acts from a holistic perspective.